Application of Digital Comic ‘History of Bestie and Bosque’ Prehistoric Period in Class X Students of SMA Negeri 10 Samarinda - Rizal Izmi Kusumawijaya; Michael Silvester Mitchel Vinco; Fathimah Dayaning Pertiwi; Syafa Aurora; Muhtada Billah Doa Syafaat (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This study aims to understand the application of digital comic media ‘Sejarah Bestie dan Bosque’ in learning prehistoric history in class X students of SMA Negeri 10 Samarinda. This research uses qualitative methodology with a case study approach. Data were obtained through interviews with both teachers and students, classroom observation and documentation. Data validity was carried out by means of data reduction, data presentation and conclusion drawing or verification. The results revealed that the use of digital comics ‘Sejarah Bestie dan Bosque’ strengthened students understanding of prehistoric material through interactive and fun visualisation. Students welcomed this digital comic as an innovative media. The results of this study are expected to provide practical insights for the development of history learning media that are more effective and relevant to technological developments, as well as input for schools to consider the integration of digital media in learning.